A DIDACTIC ITINERARY TOWARDS INTERCULTURALITY THROUGH THE NARRATIVE OF FABIO GEDA - Maria Greco, Fausto (PALIMPSEST / ПАЛИМПСЕСТ, 2016)
Moving from thoughts and impressions by Primo Levi (from his novel Hydrogen, published in The Periodic Table, 1975) about his experience at high school, the study focuses on communication from the experience in literature, especially through the age of crisis and «emergency» we are living in (as Carla Benedetti highlights in the essay called Disumane lettere, 2011). In particular, the paper tends to show the value and the vitality of humanistic knowledge in order to keep on telling and delving into reality, to regenerate perception and feelings of young people (students, teenagers) on crucial items: migrations and conditions of aliens and foreign nationals; dialogue between cultural models and religions; cross-culture, cultural mediation and interculturality. The study explains the proposal of a teaching technique experiment, moving from the reading and the analysis of two books by Fabio Geda, a very significant Italian writer, whose masterpiece Nel mare ci sono i coccodrilli (In the sea there are crocodiles, 2010) has been translated and published in thirty-two nations until now. The novel represents the journey and the struggle for survival of a young Afghan child, who traveled from his homeland to Italy, where he met the author and told about his risky and exciting adventure, after passing through Pakistan, Iran, Turkey and Greece, crossing state frontiers and cultural borders, always illegally. The other and most recent literary work by Fabio Geda is L’estate alla fine del secolo (2011), regarding both anti-Semitism and the conditions of Italian Jewish people during the twentieth century and the dialogue between generations and cultural models. Keywords: teaching technique, education, humanities, literature, interculturality, migration, Geda (Fabio).